IMPLIKATUR PERCAKAPAN HUMOR DALAM MAIN HAKIM SENDIRI: STUDI KASUS PROGRAM TV - Puspita Rahmawati; Anas Ahmadi (Indonesian language and literature education program Majapahit Islamic University, 2024)
This research examines the number of implicatures and types of conventional implicatures and non-conventional implicatures found in the TV program Main Hakim Alone. This research aims to find out how humorous conversations are formed and describe the forms of conventional implicatures and non-conventional implicatures in the TV program Main Hakim Alone. Meanwhile, the benefit of this research is that it contributes to the development of the science of pragmatics and after carrying out this research, the public will better understand the meaning contained in humorous conversations in the TV program Main Hakim Alone. Researchers looked for implicatures originating from the TV program Main Judge Alone. The research method that the researcher used used a qualitative method using an inductive thinking process which aims to gain a thorough understanding of the implicatures. The data collection technique used by researchers uses the close attention technique. The note-taking technique involves two steps, namely listening and recording data. Researchers observe or listen to audio-visual material many times to understand everything about the communication. In detail, the researcher recorded every conversation that was considered important to explain. The data analysis technique in this research uses several steps, namely watching videos and collecting data carefully, then recording and grouping the required data, then the data is analyzed and concluded as research material. Keywords: Implied, Conventional, Unconventional